CCBC Choices 2015 - Townsend, Emily McKnight; Schliesman, Megan; Lindgren, Merri V.; Horning, Kathleen T. (My University, 2015)
CCBC CHOICES is an annual list of recommended books for children and young adults selected by the librarians at the Cooperative Children's Book Center, a library of the School of Education at the University of Wisconsin-Madison. CCBC CHOICES 2015 recommends 259 titles for children and young adults published in 2014. It includes a commentary on the 2014 publishing year, including statistics on the number of books by and about people of color published for children and teens.
Keywords: multicultural literature; young adult literature; children's literature